Agricultural Youth Injuries: A Review of 2015-2017 Cases from U.S. News Media Reports. Issue 3 (3rd July 2019) - Weichelt, Bryan; Gorucu, Serap; Murphy, Dennis; Pena, Anita Alves; Salzwedel, Marsha; Lee, Barbara C.
ABSTRACT: Background : The hazardous nature of the agricultural environment, reflected in the numerous injuries and deaths to children who live, work and play on farms, coupled with the lack of a comprehensive national surveillance system in the United States, highlights the need for making the best use of publicly available youth agricultural injury data. Objective : The purpose of this study was to describe a 3-year collection of youth agricultural injuries using the publicly available injury and fatality data from AgInjuryNews.org and present recommendations for future injury prevention strategies. Methods : Data were obtained from AgInjuryNews.org, a web-based collection of U.S. news reports of agricultural injuries. We analyzed cases from 2015 to 2017 for youth aged 0–17. We classified injuries as occupational and non-occupational related, based on the Farm and Agricultural Injury Classification (FAIC) code. Each case was also coded for source and event using the Occupational Injury and Illness Classification System (OIICS). Results : Of the 348 injury reports reviewed, 51% were fatal, and about one-third of the victims were 6 years old or younger. Most injuries were non-occupational, and the most frequent injury sources were vehicles (includes tractors and all-terrain vehicles) and machinery. Youth operators, extra riders, roadway operations, and unsupervised youth playing near or in a worksite were four key contributing factors associated with vehicle and machinery related injuries. Conclusions : This study reaffirms that youth agricultural-related injuries and fatalities are still a persistent problem in the United States. The hypothesis generating AgInjuryNews system can provide more current data than traditional surveillance datasets as a tool for understanding the sources of youth agricultural injuries, monitoring injury trends, and informing policy efforts and prevention strategies. Future studies should continue to explore and evaluate the comprehensiveness of this system's data and the impact of its dissemination, as well as similar rural health informatics solutions for integration into sustainable interventions that can be customized and delivered domestically and abroad.